MANAJEMEN RISIKO PADA PENGELOLAAN DANA ZAKAT, INFAK, DAN SEDEKAH (STUDI KASUS INISIATIF ZAKAT INDONESIA (IZI) SUMATERA SELATAN) - Dimas Pandu Wizki; Rinol Sumantri; Safitri Asrol (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
The Indonesian Zakat Initiative (IZI) South Sumatra Zakat Management Institution (LAZ) is a registered and recognized institu tion by the Ministry of Religious Affairs of the Republic of Indonesia that manages zakat, infaq, and sadaqah funds. In managing ZIS funds, the Indonesian Zakat Initiative (IZI) South Sumatra faces several problems, namely collection, distribution, volunteers, and education. Risk management is a series of procedures used to identify, assess, control, and monitor risks arising from an activity. The purpose of this study is to determine the extent of risk management implementation and the risk mitigation strategies carried out by LAZ IZI South Sumatra. This study uses a qualitative method where data is collected through interviews with three main sources, namely the head of the IZI South Sumatra office, the head of the collection division, and the head of the distribution division. In addition, this study also uses the observa tion method. The results of this study indicate that the implementation of risk management by IZI South Sumatra is not yet optimal because IZI does not implement risk assessment. However, in terms of risk mitigation, the mitigation measures implemented by IZI are very good at handling existing risks.